Form of Presentation of Ranup Lampuan Dance Music in the Intat Linto Procession in Banda Aceh City - Alhari; Bondet Wrahatnala; Aris Setiawan (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
This study aims to reveal the form of presentation of ranup lampuan dance music in the intat linto baroe procession in the city of Banda Aceh. Ranup Lampuan dance music is music that is used to accompany the Ranup Lampuan dance in the procession of welcoming guests in Acehnese society. This study used a qualitative research method, a descriptive research type with an ethnomusicological approach. The results of this study reveal that the music of the ranup lampuan dance in the city of Banda Aceh is presented in several traditional events such as the intat linto procession which contains social values in the community, in the intat linto event the musicians in ranup lampuan have two roles, namely; as musicians from the guest party escorting the Linto group and as musicians for the host party (dara baroe) to accompany the ranup lamp dance. The presentation of Ranup Lampuan dance music has supporting elements, namely: Musicians, musical instruments, costumes or clothing, venues, and notations.